The Role of Social Media in Crisis Management in the Fashion Industry - Żukowska, Aniela (Rola mediów społecznościowych w zarządzaniu kryzysowym w przemyśle modowym, 2025)
The article explores the intersection of social media, crisis management, and the fashion industry. It begins by defining social media’s role in business operations, focusing on how digital platforms can be leveraged for effective crisis communication. The study highlights the challenges specific to the fashion industry, stressing the importance of aligning crisis management strategies with consumer values and expectations. Through case studies of notable controversies – Gucci’s balaclava scandal, Balenciaga’s campaigns, and Nike’s ‘Satan Shoes’ incident – the research demonstrates how quickly crises can escalate through social media, affecting brand reputation. The article identifies best practices for handling crises, such as issuing prompt statements, engaging transparently with audiences, and mitigating negative sentiments. Ultimately, it underscores the importance of proactive crisis management and the strategic use of social media to control public perception, offering insights for fashion companies to strengthen their resilience in a fast-evolving market.
Quote as: Żukowska, A. (2025). The Role of Social Media in Crisis Management in the Fashion Industry. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 195-202). Publishing House of Wroclaw University of Economics and Business.
Keywords: crisis management; social media; fashion industry; media społecznościowe; przemysł modowy; zarządzanie kryzysowe